Effects of modafinil and prazosin on cognitive and physiological functions in healthy volunteers - Winder-Rhodes, S E; Chamberlain, S R; Idris, M I; Robbins, T W; Sahakian, B J; Müller, U (Journal of psychopharmacology (Oxford), 2010)
Previous research has demonstrated cognitive-enhancing effects of modafinil in humans and generated evidence for its therapeutic potential in psychiatric disorders. The neurochemical basis of these effects remains unresolved although a role for α1-adrenoceptors has been hypothesised. In this within-subject, double-blind, placebo-controlled study, 12 healthy male adults received modafinil (300 mg), the α1-adrenoceptor antagonist prazosin (3 mg), both together and placebo on separate occasions at least 5 days apart. Cognitive effects were assessed using a well-validated testing battery focusing on executive and working memory functions. Blood pressure, heart rate and salivary α-amylase (sAA) were measured at hourly intervals. Cognitive effects of modafinil and prazosin were identified at the difficult levels of the One-Touch Stockings of Cambridge (OTSOC) planning task. Prazosin antagonized the error-reducing effect of modafinil when the agents were given together. In contrast, the combined agents acted synergistically to increase time taken to complete OTSOC problems compared with placebo. The tachycardic and sAA-elevating effects of prazosin were also potentiated by concurrent modafinil administration. The current data suggest that the cognitive effects of modafinil on performance accuracy and latency are dissociable in terms of their neurochemical mechanisms. Our findings support the hypothesised involvement of α1-adrenoceptors in some of the cognitive-enhancing effects of modafinil and warrant further investigation.